2019
DOI: 10.1080/15384101.2019.1632639
|View full text |Cite
|
Sign up to set email alerts
|

‘Patchiness’ and basic cancer research: unravelling the proteases

Abstract: The recent developments in Cathepsin protease research have unveiled a number of key observations which are fundamental to further our understanding of normal cellular homeostasis and disease. By far, the most interesting and promising area of Cathepsin biology stems from how these proteins are linked to the fate of living cells through the phenomenon of Lysosomal Leakage and Lysosomal Membrane Permeabilisation. While extracellular Cathepsins are generally believed to be of central importance in tumour progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 150 publications
(146 reference statements)
1
25
0
Order By: Relevance
“…In contrast, the migration and invasion ability of CTSK -KD was significantly reduced. This is consistent with the conclusion that Cathepsin K is highly expressed during tumor invasion and metastasis [ 39 ] and has a stimulating effect on the aggressive phenotype of various types of cancer. Soond et al [ 40 ] reported that the findings of use of utilizes combined chemotherapeutic treatment such as with Tocilizumab or Rituximab inhibited signaling transduction pathways which up-regulate the intracellular Cathepsins look very encouraging for targeting cancer.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the migration and invasion ability of CTSK -KD was significantly reduced. This is consistent with the conclusion that Cathepsin K is highly expressed during tumor invasion and metastasis [ 39 ] and has a stimulating effect on the aggressive phenotype of various types of cancer. Soond et al [ 40 ] reported that the findings of use of utilizes combined chemotherapeutic treatment such as with Tocilizumab or Rituximab inhibited signaling transduction pathways which up-regulate the intracellular Cathepsins look very encouraging for targeting cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, they can act as the base for membrane and matrix degradation, inactivation of natural protease inhibitors and chemotherapeutics, cell viability regulation, immune response modulation and inflammatory cell recruitment. [15][16][17][18] Moreover, proteases localized within the intracellular compartments, including in the cytosol, nucleus, membrane and mitochondria are associated with many signaling pathways through which they can promote: adhesion, proliferation, migration, de-differentiation and epithelial to mesenchymal transition of cancer cells. [18][19][20] The release of proteases into various cellular compartments and their altered expression can result from different factors, including the activation of membrane receptors (such as the tumor necrosis factor receptor 21 ) or the generation of reactive oxygen species.…”
Section: Proteases and Their Inhibitorsmentioning
confidence: 99%
“…The premature activation or, even intracellular activation, of other types of proteases has been demonstrated to be important mechanism to disease states through mechanisms hitherto poorly understood or scarcely investigated. 9 Premature release and activation in the cell or leaks of trypsin into the stroma may facilitate activation of enzyme cascades, leading to cellular proliferation, migration, invasion, angiogenesis, and metastasis ( Fig. 1).…”
Section: An Enemy Within: a Trojan Horse To Cancer Invasiveness?mentioning
confidence: 99%